Hubungan Stres Akademik dengan Emotional Eating pada Mahasiswa yang Sedang Mengerjakan Skripsi - Ningsih, Afcia; Mardianto, Mardianto (Lembaga Yasin AlSys, 2026)
Academic stress experienced by students during the thesis-writing stage often affects their psychological condition and everyday behavior, including a tendency toward emotional eating. This study aimed to examine the relationship between academic stress and emotional eating among students who are working on their thesis. The research employed a quantitative correlational approach with cluster sampling involving 152 students of Universitas Negeri Padang who were in the process of writing their thesis. Data were collected using an academic stress scale and an emotional eating scale, and were analyzed using the Pearson Product–Moment correlation test. The results showed a significant positive relationship between academic stress and emotional eating (r = 0.534; p = 0.000), indicating that the higher the level of academic stress, the higher the tendency toward emotional eating among students, and vice versa. These findings underscore the importance of addressing academic stress management in order to prevent emotional eating behavior that may negatively affect students’ well-being during the thesis-writing process.